A Power Conundrum: Black Women and Their Sexual Partners in the Midwest. (4th May 2019) - Gary, Faye A.; Yarandi, Hossein; Hassan, Mona; Killion, Cheryl; Ncube, Mothusi; Still, Carolyn; Hopps, June
Abstract: The purpose of this research was to determine the extent to which women of African ancestry manifested power in their relationships regarding sexual activities and to examine the influence that specific variables had on their sexual partnerships. A sample ( N  = 200) of midlife women aged 40–65, who lived in the Midwest participated in this research. The Sexual Relationship Power Scale was used to examine these relationships. Face-to-face interviews occurred in community settings. Multiple regression equations were used to examine the potential impact of specific variables on sexual functioning. Results of the analysis revealed that variables such as mental quality of life, decision-making, and health promotion were positively associated with sexual relationships. Conversely, depression and life stress scores were negatively linked to sexual relationships. Knowledge gained from this research could be used to explore the phenomena of power as expressed in the daily lives of women of African descent. The research can also be discussed from the perspective of a "Black tax, " that has burdened Black women for centuries and is manifested through years of discrimination, bias, and the lack of equity in most domains of American institutions.